Bifid Mandibular Canal: A Proportional Meta-Analysis of Computed Tomography Studies - Nyan Min Aung; Kyaw Kyaw Myint (Hindawi Limited, 2023)
Introduction. Growing body of evidences showed different grades in prevalence of bifid mandibular canals. Because the previous reviews focused solely on patient-level occurrence, hemi-mandible-level prevalence, bilateral symmetry, length, and diameter of bifid mandibular canals were required to be estimated collectively. The research question of this meta-analysis was "What is the prevalence of bifid mandibular canal among patients seeking computed tomography examinations"? Materials and Methods. In vivo, computed tomography, and cross-sectional studies were eligible. Studies, with less than 100 subjects or anatomic site restriction or controlled class of bifid mandibular canal, were excluded. Joanna Briggs Institute (JBI) critical appraisal tool for prevalence studies was used to assess methodological quality of all included studies. Random effect meta-analyses for proportion of bifid mandibular canal were done. Results. 40 studies met the inclusion criteria. All studies were selected for both systematic review and meta-analyses. Totally, 17714 patients and 31973 hemi-mandibles were included. All eligible studies showed moderate risk of bias on average. Resulting from the random effect model, more than 20% of patients seeking computed tomographic examinations had bifid mandibular canals (BMCs) which penetrated into slightly more than 14% of hemi-mandibles. Of the patients having bifid mandibular canals (BMCs), nearly 23% exhibited such anatomy on both sides of their mandibles. Estimated mean length and diameter of the accessory canals of bifid mandibular canals were 12.17 mm and 1.54 mm, respectively. Conclusion. The geographical locations, classifications, reliability test, and voxel size of computed tomography were all implicated in the prevalence of bifid mandibular canals along with gender and laterality, although considerable heterogeneity and bias were detected.